Comparative analysis of gender related farm households in the Arsi-Negele farming zone in Ethiopia - Duvel, G.H. (Gustav Heinrich) (University of Pretoria, 2013)
Dissertation (MSc (Agricultural Extension))--University of Pretoria, 2005.